(untitled) (The Review of Diabetic Studies, 2025)
The study adopted the descriptive analytical approach because it was suitable for its objectives, and used a questionnaire consisting of two main axes: occupational safety culture and the level of professional performance. The instrument’s validity and reliability were verified using Cronbach’s alpha coefficient, and the results showed a high degree of internal consistency. The results revealed that the level of occupational safety culture among the sample group was high, reflecting the organization’s interest in implementing prevention and safety procedures and training employees on them regularly. It was also found that the level of professional performance was high, as employees demonstrated a clear commitment to quality and accuracy standards in performing field tasks. The correlation coefficient results showed a strong and statistically significant positive relationship between occupational safety culture and the level of professional performance, confirming that promoting awareness and implementing safety procedures directly contribute to raising performance efficiency. The study recommended the need to continue preventive training programs and intensify occupational safety awareness campaigns, in addition to integrating safety concepts into performance evaluation standards to ensure a safer and higher-quality work environment.